PENGEMBANGAN BUKU AJAR MENULIS PUISI BERORIENTASI CINTA TANAH AIR SISWA KELAS X SMA - Saputro, Agung Nasrulloh (Widyabastra, 2012)
This resesarch is the development research that try to develop a writing poetry textbook oriented on patriotic aspects. this development research refers to the models from Borg and Gall. the model consists of ten stages of development, namely the stage of research and gathering initial information, the stage of planning, the stage of developing the format of initial information, the stage of initial testing, the stage of revising product, the stage of field trials, The stage of revising stage, the stage of field trials, the ending stage of revising product, and the stage of dissemination and implementation. The research just reached the stage of revising the final product without including the stage of dissemination and implementation due to limited research time. In general, this study aims to describe the process of development, quality, implementation, and effectiveness of writing poetry textbook oriented on patriotic aspect.The results of the textbook development process is shown in stages as follows. the Validation of textbook is assessed by three validators, the result of validation indicates that the textbook is categorised as a good one, because its percentage is greater than or same as 75%, the results of early trials is tested on a limited basis to the seven students of X ten grades generated with questionnaire, interview, and observation. Based on the results of field trials, it gained that the average score of the students in writing poetry is 79.2. The results of field tests generated studets questionnaire, interview by teacher, observation in order to create an excellent textbook.Key words: Development, Writing Poetry, and Patriotic aspect.